Pan-cancer analysis of the FAM83 family and its association with prognosis and tumor microenvironment - Yuan, Shangkun; Huang, Zhisheng; Qian, Xiaoying; Wang, Yong; Fang, Chen; Chen, Renfang; Zhang, Xinwei; Xiao, Zhehao; Wang, Qian; Yu, Biao; Li, Yong (Frontiers in Genetics, 2022)
Family with sequence similarity 83 (FAM83) is a newly identified family of oncogenes whose members play important roles in signaling and cancer progression. However, a thorough understanding of the FAM83 family in tumors is still lacking. Here, we performed a comprehensive analysis of the expression levels of the FAM83 family across cancers and patient prognoses using bioinformatics methods. We found that the expression levels of FAM83 family genes were upregulated in most tumors, and importantly, high expression levels of FAM83 family genes were related to poor prognosis in most tumors. In addition, we analyzed the relationship of FAM83 family genes with immune subtypes and the tumor microenvironment (TME). The results showed that FAM83 family genes were significantly associated with immune infiltrative subtypes and to varying degrees with the level of stromal cell infiltration and tumor stem cells. Finally, our study also showed the relationship between FAM83 family genes and drug sensitivity. Therefore, this pan-cancer analysis demonstrates the critical role of FAM83 family genes in tumor development and provides new clues for therapeutic strategies for cancer.